Rethinking the Atrocities Act: Proving Prejudice and Interpreting Evidence in Rajasthan - Sandhya Fuchs (South Asia Multidisciplinary Academic Journal)
India’s Prevention of Atrocities Act (PoA), which aims to punish and prevent violence against Dalits (ex-untouchables) and Adivasis (tribals), represents one of the most ambitious hate crime laws in the world. However, concerns regarding its effectiveness in addressing historical oppression dominate Indian public debates. Based on extensive ethnographic fieldwork with Dalit atrocity survivors and police and judiciary in Rajasthan, this article proposes that current critiques of the PoA have neglected to address fundamental questions about the ideas of social transformation that underpin this unique law. This paper analyses how legal evidence regimes can obscure realities of hate. It further examines to what extent the institutional barriers facing atrocity complainants reflect deeper challenges, which haunt hate crime laws and legislative attempts to address inequality on a global level. Ultimately, the article reveals that for the PoA to be “effective,” policymakers must first decide to whose definition of justice and success the act is accountable.